Asymptomatic Bacteriuria Escherichia coli Are Live Biotherapeutics for UTI - Rudick, Charles N. (PLoS One, 2014)
Urinary tract infections (UTI) account for approximately 8 million clinic visits annually with symptoms that include acute pelvic pain, dysuria, and irritative voiding. Empiric UTI management with antimicrobials is complicated by increasing antimicrobial resistance among uropathogens, but live biotherapeutics products (LBPs), such as asymptomatic bacteriuria (ASB) strains of E. coli, offer the potential to circumvent antimicrobial resistance. Here we evaluated ASB E. coli as LBPs, relative to ciprofloxacin, for efficacy against infection and visceral pain in a murine UTI model. Visceral pain was quantified as tactile allodynia of the pelvic region in response to mechanical stimulation with von Frey filaments. Whereas ciprofloxacin promoted clearance of uropathogenic E. coli (UPEC), it did not reduce pelvic tactile allodynia, a measure of visceral pain. In contrast, ASB E. coli administered intravesically or intravaginally provided comparable reduction of allodynia similar to intravesical lidocaine. Moreover, ASB E. coli were similarly effective against UTI allodynia induced by Proteus mirabilis, Enterococccus faecalis and Klebsiella pneumoniae. Therefore, ASB E. coli have anti-infective activity comparable to the current standard of care yet also provide superior analgesia. These studies suggest that ASB E. coli represent novel LBPs for UTI symptoms.